1995
DOI: 10.1016/0014-5793(95)01193-i
|View full text |Cite
|
Sign up to set email alerts
|

Fast solute release from photosensitive liposomes: an alternative to ‘caged’ reagents for use in biological systems

Abstract: The kinetics of release of soluble marker trapped in liposomes of gel phase phospholipid containing a photoisomerisahie phospholipid analogue have been investigated. Marker release is triggered by UV laser flash photolysis at 355 nm. A markedly temperature-dependent release rate is seen, and above 25°C millisecond release kinetics can be achieved. These results suggest that such liposomes might find application as an alternative to conventional 'caged' reagents for photo-triggered reagent release in biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 15 publications
0
34
1
Order By: Relevance
“…Eastoe and co-workers [17] developed an emulsion system which was photo-responsive and could be used in lithography. Vesicles formed from photo-sensitive surfactants were employed in drug delivery systems and fulfilled the purpose of targeted and controlled release by light [18]. Faul and co-workers [19,20] found that highly organized functional materials can be obtained simply by ionic self-assembly (ISA) based on multiply charged dye molecules and oppositely charged surfactants, which provided a facile route to synthesize functional materials with optical properties for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Eastoe and co-workers [17] developed an emulsion system which was photo-responsive and could be used in lithography. Vesicles formed from photo-sensitive surfactants were employed in drug delivery systems and fulfilled the purpose of targeted and controlled release by light [18]. Faul and co-workers [19,20] found that highly organized functional materials can be obtained simply by ionic self-assembly (ISA) based on multiply charged dye molecules and oppositely charged surfactants, which provided a facile route to synthesize functional materials with optical properties for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The principles of phototriggering include photopolymerization of lipids, 13 photosensitization by membrane-anchored hydrophobic probes, [14][15][16] or photoisomerization of photoreactive lipids. 17 To date, none of the lipid formulations developed have been successfully demonstrated for in vivo phototriggering applications. Lack of adequate photon energy produced by the light source(s) or the inability of light to penetrate into biological tissues appear to be the most common roadblocks that have hampered the success of phototriggerable liposomal platforms in vivo.…”
Section: 10mentioning
confidence: 99%
“…On photoisomerization with ultraviolet light a photostationary state dominated by the more bulky Z-isomer of the azobenzene moieties is formed. Solute release rates after UV exposure are markedly sensitive to temperature, and millisecond release kinetics can be achieved (8,9) especially when the bilayer membrane contains cholesterol which enhances the release rate of trapped marker dye (10). Liposomes containing Bis-Azo PC in the absence of cholesterol show a threshold of photoisomerization below which leakage of trapped marker dye is not seen.…”
mentioning
confidence: 98%
“…Below about 3% of Bis-Azo PC (mol:mol), no leakage of trapped marker is seen on UV photolysis. The threshold effect has been studied by pulsed laser experiments in our earlier work (8). It was shown that samples containing Bis-Azo PC could be exposed to several lowintensity UV pulses without significant leakage of contents, but that rapid leakage ensued after a sufficient number of such exposures or above a threshold intensity.…”
mentioning
confidence: 98%